Current tensions and trends in the world scientific system - Beigel, Maria Fernanda (2014)
A truly global publishing system came along in the 1990s and a new path of academic dependency was extended within peripheries. During the implementation of neoliberal policies in the Latin American universities, increasing scarce resources oriented scientists to foreign funds and research agendas became determined heteronomously. The paper in refereed journals replaced the book which had been the principal media for academic dialogue until then (Beigel, 1995). Peer reviewed and Indexed journals published in English became the main reward in a system increasingly centralized towards the US as an attraction center for postgraduate studies, research funding and publishing.